How to find meaning: A journey toward a Living Lab for People - Habermann, Birgit; Valencia Leñero, Eva Maria; Nehring, Ryan (2023)
Sometimes projects introduce a new concept that has, at the outset, little meaning other than a word. And then through engagement of different scientists, stakeholders and partners working together, this word acquires real meaning and starts becoming an actionable concept. This process is not always smooth and requires a lot of patience, confidence and respect for each other’s different opinions, interests, schools of thoughts and positionalities – and if operating on a global level, also for different cultures.